M. tuberculosis Induces Potent Activation of IDO-1, but This Is Not Essential for the Immunological Control of Infection - Blumenthal, Antje; Nagalingam, Gayathri; Huch, Jennifer H.; Walker, Lara; Guillemin, Gilles J.; Smythe, George A.; Ehrt, Sabine; Britton, Warwick J.; Saunders, Bernadette M. (PLOS ONE, 2012)
Indoleamine 2,3-dioxygenesae-1 (IDO-1) catalyses the initial, rate-limiting step in tryptophan metabolism, thereby regulating tryptophan availability and the formation of downstream metabolites, including picolinic and quinolinic acid. We found that Mycobacterium tuberculosis infection induced marked upregulation of IDO-1 expression in both human and murine macrophages in vitro and in the lungs of mice following aerosol challenge with M. tuberculosis. The absence of IDO-1 in dendritic cells enhanced the activation of mycobacteria-specific T cells in vitro. Interestingly, IDO-1-deficiency during M. tuberculosis infection in mice was not associated with altered mycobacteria-specific T cell responses in vivo. The bacterial burden of infected organs, pulmonary inflammatory responses, and survival were also comparable in M. tuberculosis-infected IDO-1 deficient and wild type animals. Tryptophan is metabolised into either picolinic acid or quinolinic acid, but only picolinic acid inhibited the growth of M. tuberculosis in vitro. By contrast macrophages infected with pathogenic mycobacteria, produced quinolinic, rather than picolinic acid, which did not reduce M. tuberculosis growth in vitro. Therefore, although M. tuberculosis induces robust expression of IDO-1 and activation of tryptophan metabolism, IDO-1-deficiency fails to impact on the immune control and the outcome of the infection in the mouse model of tuberculosis.